THE CHALLENGES OF GRAMMATICAL TRANSFORMATION IN TRANSLATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The lesson presents a contemporary understanding of the primary issues with translation and the field of translation studies. papers on translation theory in the sciences. Based on the factual material translation process, methods for completing certain translation jobs are presented, highlighting lexical-semantic, grammatical, and stylistic issues. Examples are utilized as reference points for the English to Uzbek-translations.